Embracing responsible innovation and empowering consumers in the digital age - Douglas J. Cumming; Sofia Atiqah Johan (Asian Development Bank Institute (ADBI), 2020)
We examine the intersection between financial inclusion, financial literacy, and financial technology. Using worldwide data, we find a significant positive relation between the World Bank's "Findex" measures and various measures of financial literacy, as well as Google Trends. We show that e-commerce legislation around the world significantly positively facilitates fintech adoption. We further examine Google Scholar to identify gaps in the research in specific regions. Finally, we use more specific information from one type of fintech-crowdfunding-to show that financial literacy indeed facilitates fintech and to explain the specific mechanisms therein. We discuss the policy and research implications based on our data and provide an overview of the literature to date.
Keywords: G20; G53; 330; fintech; financial inclusion; financial literacy